CAPITAL EXPENDITURE AND INFLATION: IS GOVERNMENT SPENDING WORSENING NIGERIA’S ECONOMIC CRISIS? - Abass Adewale (Universitas Kuningan, 2025)
This study examines Nigeria's inflation and government capital expenditures from 1991 and 2023. This study examines if government spending on administration, economic services, social and community services, and government transfers has increased or decreased the country's inflation rate. Secondary data from the Central Bank of Nigeria's statistical bulletin was gathered for the study using an ex-post facto research design. To determine the degree to which each category of spending influences the rate of inflation, the study used the Autoregressive Distributed Lag (ARDL) model. The research results demonstrate limited and non-significant links between different expenditure types and inflation while economic services spending generates the most insignificant negative correlation. Increasing capital expenditure during recent years has not reduced high inflation because the existing spending practices appear inadequate to fight inflationary trends. As per the research economic services budget shows some responsiveness to inflation reduction yet it generates no statistically meaningful effects. In contrast, administration, social/community services, and government transfers expenditure show minimal impact on inflation. The study establishes that capital expenditure supports national development but Nigeria's present capital spending system and management tactics fail to solve inflation problems properly. Managed fiscal policy implementations that specifically support macroeconomic priorities need to become the focus to fight inflation while establishing enduring economic equilibrium. Better planning together with expenditure prioritization by government is essential for Nigeria to overcome its economic crisis according to findings from this study.